2011
DOI: 10.1038/pj.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Creation of persistent charge-transfer interactions in TCNQ polyester

Abstract: A 7,7,8,8-tetracyanoquinodimethane polyester was converted into a strongly colored polyester with low-energy charge-transfer (CT) bands by treatment with electron-rich alkyne molecules under mild conditions. The post-functionalization was monitored by its ultraviolet-visible-near infrared (IR) spectra, which suggested a quantitative addition reaction without any side reactions. This result was further supported by 1 H and 13 C nuclear magnetic resonance, IR and elemental analyses. The functionalized polymer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
3
26
0
1
Order By: Relevance
“…A similar result was observed for the postfunctionalization of polythiophene derivatives [25]. This study also suggested that the use of stronger acceptor molecules, such as 7,7,8,8-tetracyanoquinodimethane (TCNQ) and its derivatives [26][27][28][29][30][31][32][33][34], is effective for the dramatic lowering of the LUMO levels or the enhancement of the n-type characteristics.…”
Section: Introductionsupporting
confidence: 76%
“…A similar result was observed for the postfunctionalization of polythiophene derivatives [25]. This study also suggested that the use of stronger acceptor molecules, such as 7,7,8,8-tetracyanoquinodimethane (TCNQ) and its derivatives [26][27][28][29][30][31][32][33][34], is effective for the dramatic lowering of the LUMO levels or the enhancement of the n-type characteristics.…”
Section: Introductionsupporting
confidence: 76%
“…[35] However,t he F 4 TCNQ adducts gradually decomposed upon contact with glass surfaces to form green, insoluble products.T oa void this decomposition, the glassware was deactivated by silylation with dimethyldichlorosilane (DMDCS). [36] Thed icyanovinyl moiety was shown to be the minimal structural unit required for the CA-RE reactions.Aseries of dicyanovinyl (DCV) derivatives were prepared and their reactivities investigated under identical conditions (in DMF at 100 8 8C). [36] Thed icyanovinyl moiety was shown to be the minimal structural unit required for the CA-RE reactions.Aseries of dicyanovinyl (DCV) derivatives were prepared and their reactivities investigated under identical conditions (in DMF at 100 8 8C).…”
Section: Alkene Acceptors In the Ca-re Reactionmentioning
confidence: 99%
“…Since the TCNQ moieties were good acceptors for the click reactions, they were quantitatively converted into the D-A chromophore by the addition of the small alkyne molecule, 4,4€-(ethyne-1,2-diyl)bis(N,N-dimethylaniline) (see Figure 20). 86 Although there were two possibilities of E-and Z-isomer products on the D-A chromophore unit, all the spectroscopic characterizations and computational calculations suggested that the Z-form is more stable than the corresponding E-form. The max of the precursor TCNQ polyester appeared at 412 nm in 1,2-dichlorobenzene, whereas the post-functionalized TCNQ polyester exhibited the red-shifted max at 623 nm due to the intramolecular CT interactions.…”
Section: +mentioning
confidence: 99%